Financial constraints and public funding for eco-innovation: Empirical evidence on European SMEs - Grazia Cecere; Nicoletta Corrocher; Maria Luisa Mancusi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
Financial constraints have an important impact on the development of eco-innovations, but their effect varies according to the type of funds taken into account. This article studies the impact of the lack of funds on the development of eco-innovations, distinguishing between internal, external and public funds. In particular, we investigate the interaction between public funding, on the one hand, and internal and other external sources of funding. The empirical analysis is based upon a sample of European SMEs belonging to different sectors that are involved in products, processes and organizational eco-innovations. Our results show that a lack of internal funding always decreases the probability to introduce eco-innovations, while the lack of private external funds does not appear to hinder the development of eco-innovations. Interestingly, we find that access to public funds or incentives is effective in improving a firm's ability to introduce eco-innovations, but only when the firm is not short of funds (either from internal or external sources), thus suggesting that public funds are somewhat complementary to other funds. Further analysis shows that these effects are mostly relevant in small firms.
Keywords: O31; Q55; G38; 330; eco-innovations; public funding; financial constraints; SMEs